2016
DOI: 10.1186/s12889-016-2769-7
|View full text |Cite
|
Sign up to set email alerts
|

Community referral for presumptive TB in Nigeria: a comparison of four models of active case finding

Abstract: BackgroundEngagement of communities and civil society organizations is a critical part of the Post-2015 End TB Strategy. Since 2007, many models of community referral have been implemented to boost TB case detection in Nigeria. Yet clear insights into the comparative TB yield from particular approaches have been limited.MethodsWe compared four models of active case finding in three Nigerian states. Data on presumptive TB case referral by community workers (CWs), TB diagnoses among referred clients, active case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
2
26
1
Order By: Relevance
“…This could be a result of WDA leaders who have regular meeting and discussion with HEWs might further created awareness on HH contacts about TB and improved their health seeking behavior for TB screening. Contribution of such active participation of community members were also revealed in other related studies [27,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 72%
“…This could be a result of WDA leaders who have regular meeting and discussion with HEWs might further created awareness on HH contacts about TB and improved their health seeking behavior for TB screening. Contribution of such active participation of community members were also revealed in other related studies [27,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 72%
“…The NTBLCP guidelines stipulated that treatment supporter can be a relation or someone (volunteer) close to the patient's home and has been trained to provide support for TB patients on treatment [14]. A study from Nigeria showed that few of the community volunteers served as treatment supporter and the community TB care in the country was not effective [15]. Studies from West and East Africa, Asia and South America have shown that the use of family members as treatment supporters was effective [16]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although, there are controversies about the effectiveness and efficiency of supervision of health care services deliveries (Bosch-Capblanch and Garner, 2008), however, more evidences back the claim that supportive supervision could improve performance of health systems (Tegegne et al, 2018). As it has been employed in several other contexts, supportive supervision could be a viable managerial tool to improving health systems performance and in programs such as the MSS/SURE-P MCH (Adejumo et al, 2016). Supportive supervision has been reported to improving routine immunization activities in recent past in Nigeria (O'Connell and Wonodi, 2016).…”
Section: Discussionmentioning
confidence: 99%